Perancangan Video Promosi Sekolah Rimba Indonesia (SRI) untuk Orang Tua yang Memiliki Anak Usia 6-7 Tahun di Kota Bandung - Rizkiani, Meti Agni; Putra, Iqbal Ridwanto; Purbasari, Sophia (Universitas Informatika dan Bisnis Indonesia, 2024)
This research designed a promotional video for Sekolah Rimba Indonesia for parents of children aged 6-7 years in Bandung City. Sekolah Rimba, which was founded in 2021, focuses on non-formal education that develops students' interests, talents and life skills through interaction with nature. Promotional videos were chosen as the main media because they are more effective in conveying information than text. The research method used is qualitative with observation, interviews and literature studies to dig up in-depth information about this school. Promotional videos and additional media, such as trailers and Instagram feed designs, are designed to increase public awareness of Jungle School. This campaign aims to attract parents to register their children and support Rimba School as an innovative education center in Indonesia.